Analisis Algoritma J48 Pada Pengambilan Keputusan Pemberian Pinjaman Kepada Calon Nasabah - Agnes Irene Silitonga; Lukas Ginting; Enjelina Sinaga; Elson Zega; Samuel Sembiring; Yoakim Simamora (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2024)
This research aims to analyze the stages of decision making for granting loans to prospective customers using the J48 Algorithm. Using the "Loan-Approval-Prediction-Dataset" dataset obtained from Kaggle, this research will build a decision tree model that can provide insight into the key factors that influence the decision. It is hoped that the results of this research can contribute to financial institutions in increasing accuracy, efficiency and objectivity in the credit evaluation process, as well as helping prospective customers understand the factors that need to be considered to increase their chances of loan approval.